2020
DOI: 10.20885/jkki.vol11.iss3.art9
|View full text |Cite
|
Sign up to set email alerts
|

N Terminal-Pro B Type Natriuretic Peptide (NT- PRO BNP) levels and severity of disease in elderly with heart failure

Abstract: Background: Heart failure is a major health problem in the world. It is associated with high morbidity and high mortality especially in elderly patients. Most studies reported that N terminal pro-B type natriuretic peptide (NT-proBNP) is used in the diagnosis of heart failure, but tests in determining severity levels of heart failure in the elderly remains unclear.Objective: This study is to determine differences of NT-pro BNP levels based on severity of heart failure in elderly patients. Methods: This was an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Marfianti, Fauziyati, and Hisyam (15) found that male NT-pro BNP levels were higher than female patients, and NT pro-BNP levels in those aged> 70 years were higher than those aged less than 70 years.…”
Section: Discussionmentioning
confidence: 96%
“…Marfianti, Fauziyati, and Hisyam (15) found that male NT-pro BNP levels were higher than female patients, and NT pro-BNP levels in those aged> 70 years were higher than those aged less than 70 years.…”
Section: Discussionmentioning
confidence: 96%